Mediating Effect of Islamic Social Reporting on the Relationship between Good Corporate Governance and Company Value: The Case of the State-Owned Enterprises - Indah Yuliana; Farahiyah Sartika (Global Review of Islamic Economics and Business, 2020)
The concept of Good Corporate Governance (GCG) is related to the disclosure of Islamic Social Reporting (ISR) which guarantees that the funds invested in the company are well managed and will provide adequate returns so that this can attract investors and indirectly can increase the company value. This research aims to analyze the indirect effect of GCG rating on company value through the disclosure of ISR and it also attempts to analyze the direct effect of GCG and ISR toward company value, and the effect of GCG towards ISR. This research used quantitative and descriptive approaches with secondary data. The state-owned enterprises in the manufacturing and mining sector listed in the Indonesian Sharia Stock Index (ISSI) were selected as the sample of the study. The method used in this study includes descriptive statistical analysis, partial least square, and mediation test. The result shows that GCG has a positive effect on company value and ISR disclosure, while ISR disclosure does not affect company value. However, GCG does not affect company value through ISR disclosure. This indicates that ISR disclosure has no mediation effect on the relationship between GCG and company value.